Effect of resin thickness on the microhardness and optical properties of bulk-fill resin composites - Eun-Ha Kim; Kyoung-Hwa Jung; Sung-Ae Son; Bock Hur; Yong-Hoon Kwon; Jeong-Kil Park (Korean Academy of Conservative Dentistry, 2015)
Objectives This study evaluated the effects of the resin thickness on the microhardness and optical properties of bulk-fill resin composites. Methods Four bulk-fill (Venus Bulk Fill, Heraeus Kulzer; SDR, Dentsply Caulk; Tetric N-Ceram Bulk Fill, Ivoclar vivadent; SonicFill, Kerr) and two regular resin composites (Charisma flow, Heraeus Kulzer; Tetric N-Ceram, Ivoclar vivadent) were used. Sixty acrylic cylindrical molds were prepared for each thickness (2, 3 and 4 mm). The molds were divided into six groups for resin composites. The microhardness was measured on the top and bottom surfaces, and the colors were measured using Commission Internationale d'Eclairage (CIE) L*a*b* system. Color differences according to the thickness and translucency parameters and the correlations between the microhardness and translucency parameter were analyzed. The microhardness and color differences were analyzed by ANOVA and Scheffe's post hoc test, and a student t-test, respectively. The level of significance was set to α = 0.05. Results The microhardness decreased with increasing resin thickness. The bulk-fill resin composites showed a bottom/top hardness ratio of almost 80% or more in 4 mm thick specimens. The highest translucency parameter was observed in Venus Bulk Fill. All resin composites used in this study except for Venus Bulk Fill showed linear correlations between the microhardness and translucency parameter according to the thickness. Conclusions Within the limitations of this study, the bulk-fill resin composites used in this study can be placed and cured properly in the 4 mm bulk.